JIKO (Jurnal Informatika dan Komputer) : An Application Of Rough Set Theory To Cluster Student Assessment At Universities - Suhirman (STMIK AKAKOM, 2017)
Assessment is the last session of a lecture in college. There are several components that form the basis of calculations. A technique to select a clustering attribute based on rough set theory is presented. Dataset is taken from a survey of 150 architectural design studio students. Data are taken on 6th semester students majoring in architecture University of Technology of Yogyakarta Indonesia.